Evaluasi Penggunaan Antibiotik Profilaksis pada Pasien Sectio Caesarea di RSUD Budhi Asih Periode Juni-Desember 2020 - Pratiwi, Ritha Widya; Simanjuntak, Yenny Yosalina; Veriyanti, Putu Rika (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Sectio Caesarea (SC) surgical patients are given prophylactic antibiotics to prevent surgical wound infections (SWIs). This study aimed to determine the pattern of use of prophylactic antibiotics in SC surgical patients at Budhi Asih Hospital. This research used a descriptive research type with a cross sectional approach. Number of samples 201 medical records with retrospective data collection. The patient inclusion criteria used were patients delivered by Sectio Caesarea and the patients who had a complete medical record. The results showed that the characteristics of Sectio Caesarea surgical patients at were based on age ≤ 20 years were 14 people (7%), were based on age of 21–34 years there were 133 people (66.2%), and were based on age ≥ 35 years old as much as 54 peoples (26.9%). Based on parity 1-2 people as 114 peoples (56.7%) and parity ≥ 3 people as 87 peoples (43.3%). Based on the history of SC 1-2 times as many as 193 people (96%) and ≥ 3 times as many as 8 people (4%). Based on the prescription pattern using ceftriaxone as many as 200 people (99.5%) and those using amoxicilin as many as 1 person (0.5%). Based on the route of prophylactic antibiotics intravenously, it was 200 people (99.5%) and orally 1 person (0.5%). Based on the time and frequency of prophylactic antibiotics, 201 people (100%) were given. Based on the duration of antibiotics, 201 people (100%) were not added prophylactic antibiotics. Based on the duration of surgery ≤ 60 minutes is 201 people (100%). Based on the Surgical Site Infection(SSI), those who experienced the SSI were 2 people (1%) and those who did not experience the SSI were 199 people (99%). The prophylactic antibiotics used were ceftriaxone with a dose of 1-2 grams/day, the time for drug administration was appropriate 30-60 minutes before surgery, appropriate antibiotics were given intravenously.